Power-switching converters - Ang, Simon S., ....-; Oliva, Alejandro, ....- (Boca Raton (Fla.) : Taylor and Francis, 2005)
Power-Switching Converters provides detailed, practical coverage of switching converters, from the fundamental principles to the next generation of programmable devices. It examines buck, boost, quasi-resonant, loaded-resonant, and isolated configurations. The authors also compare the advantages of switching converters over conventional converters. This new edition includes new material and references, brings all chapters up to date, and provides two new chapters on interleaved converters and switched capacitor converters. The authors furnish new case studies and have also added the discrete-time modeling method to the discussion of the dynamic analysis of switching converters.
After nearly a decade of success owing to its thorough coverage, abundance of problems and examples, and practical use of simulation and design, Power-Switching Converters enters its second edition with new and updated material, entirely new design case studies, and expanded figures, equations, and homework problems. This textbook is ideal for senior undergraduate or graduate courses in power electronic converters, requiring only systems analysis and basic electronics courses. The only text of such detail to also include the use of PSpice and step-by-step designs and simulations, Power-Switching Converters, Second Edition covers basic topologies, basic control techniques, and closed-loop control and stability. It also includes two new chapters on interleaved converters and switched capacitor converters, and the authors have added discrete-time modeling to the dynamic analysis of switching converters. The final two chapters are dedicated to simulation and complete design examples, respectively. PSpice examples and MATLAB scripts are available for download from the CRC Web site. These are useful for the simulation of students' designs. Class slides are also available on the Internet. Instructors will appreciate the breadth and depth of the material, more than enough to adapt into a customized syllabus. Students will similarly benefit from the more than 440 figures and over 1000 equations, ample homework problems, and case studies presented in this book.
Includes bibliographical references and index.
Keywords: Electric current converters; Power electronics; Statische omzetters; Switching circuits; Vermogenselektronica